(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
In medicine, oil obtained from amaranth (Amaranthus) is used widely to alleviate gastric and intestinal ulcers, treat skin diseases, accelerate the healing of incised wounds, and manage radiation-related illnesses. Notably, amaranth seeds are extensively employed as a medicinal agent to help prevent the growth and promote the resorption of malignant tumours associated with cancer. Medicinal amaranth belongs to the group of therapeutically valuable plants. This thesis discusses the plant’s medicinal properties and methods of cultivation.